Risk factors and prevention of placenta-associated diseases - Ekaterina A. Minaeva; Roman G. Shmakov (IP Berlin A.V., 2021)
The review presents modern data on the preventive effect of antiplatelet and anticoagulant therapy of placenta-associated diseases. The review includes data from foreign and Russian articles published over the past 15 years on the Scopus, Web of Science, MedLine, The Cochrane Library, EMBASE, Global Health, CyberLeninka, Pubmed databases. In recent years, there have been reports of the effectiveness of low molecular weight heparins in the prevention of placenta-associated complications. M. Rodger et al. In their study (2016), report on the effect of low molecular weight heparins on the development of placenta-associated complications. Patients whose previous pregnancy was complicated by preeclampsia or fetal growth restriction were randomized into 2 groups. The first group of pregnant women began to receive injections of low molecular weight heparins at an early stage of pregnancy (before 12 weeks), the second group did not receive low molecular weight heparins. Thus, only 19% of women receiving low molecular weight heparin therapy and 43% of women not receiving it developed placenta-associated complications, which may indicate the effectiveness of low molecular weight heparins. This data shows the urgency of the problem of placenta-associated complications, and the development of effective methods of early prevention of these diseases can improve the outcomes of the pregnancy.